SIMBOLISASI PEREMPUAN JAWA DALAM NOVEL 'GADIS KRETEK' KARYA RATIH KUMALA DARI PERSPEKTIF FEMINISME EKSISTENSIAL - Putri, Ardilla Aulia; Qomariyah, U'um (UNIVERSITAS PGRI YOGYAKARTA, 2024)
The symbolization of Javanese women has a broad scope and is divided into several aspects of life, both in terms of appearance, placement and ideas. An alternative solution to this problem is to fight back regarding the symbolization experienced by Javanese women in reading, one of which is literary works. This research aims to describe the form of symbolization of Javanese women and the form of resistance to the symbolization of Javanese women found in the novel Girl Kretek by Ratih Kumala. This researcher used a qualitative descriptive research method with an existential feminist approach. The data collection in this research was carried out using library study techniques and note-taking techniques. The research results show (1) there are 4 types of symbolization of Javanese women in the novel, namely symbolization of Javanese women in the form of actions, words, objects and natural phenomena; and (2) there are 4 forms of women's resistance to the symbolization of Javanese women in the novel using Simone de Beauvoir's existential feminism approach, including working for the character Roemaisa, becoming an intellectual woman for the character Dasiyah, working for the goal of socialist transformation of society for the character Dasiyah, and rejecting otherness in the character Roemaisa figure. The results of the research can broaden insight and be used as a means of raising awareness of the importance of women's freedom and rights. Then, this article can be used as reference material for students, especially in the field of literature.